Game Real-Time Strategy Galactic Defense Berbasis iOS - Therry, Bobby William; Andjarwirawan, Justinus; Liliana, Liliana (Jurnal Infra, 2015)
With the rapid development of technology, the need of entertainment keeps going up. On the other hand activities and businesses among the vast majority of people are increasing. The existence of smartphone helps a lot of people to increase their productivity. Besides the general function of it, smartphone can also be used for gathering information and as an entertainment system.Android and iOS are the top 2 operating system that most people used. Using a game engine called Cocos2d, a game will be made for iOS operating system. Artificial intelligence with Finite State Machine method will be applied to this game on 5 NPCs, since the game is intended for single-player.With SpriteBuilder as an editor for user interface, Objective-C as the programming language and Xcode as IDE. A video game called Galactic Defense has been created by adapting its concept from a traditional game called "Bentengan" (or Fortress in English) which has been modified to adjust the handheld device. This game has 2 difficulty levels and a save game feature.